Letter to Jane Tolmach from Assemblyman Eugene T. Gualco - Eugene T. Gualco:::::: (1976)
In a June 21, 1976 letter, Assemblyman Eugene T. Gualco congratulated Jane Tolmach on winning the Assembly nomination. He expressed confidence that she would also be successful in the general election and said he looked forward to working with her in the Assembly. Gualco offered his assistance and extended congratulations on her victory.